Impact of binary waterborne mixtures of nickel and zinc on hypothalamic-pituitary-testicular axis in rats (2019)
Several evidences from the literature showed that the coexistence of nickel and zinc in polluted waters is related to the similarity in their geogenic and anthropogenic factors. Although most environmental exposures to metals do not occur singly, there is a paucity of scientific knowledge on the effects of zinc and nickel co-exposure on mammalian reproductive health. The present study investigated the influence of co-exposure to nickel and zinc on male reproductive function in rats. Experimental rats were co- exposed to environmentally relevant concentrations of waterborne nickel (75 and 150 mg NiCl2 L-1) and zinc (100 and 200 mg ZnCl2 L-1) for 45 successive days. Subsequently, reproductive hormones were assayed whereas the hypothalamus, epididymis and testes of the rats were processed for the assessment of oxidative stress and inflammation indices, caspase-3 activity and histology. Results indicated that co- exposure to nickel and zinc significantly (p < 0.05) abolished nickel-mediated diminution of antioxidant defense mechanisms while diminishing levels of reactive oxygen and nitrogen species and lipid per- oxidation in the hypothalamus, epididymis and testes of the exposed rats. Additionally, co-exposure to zinc abated nickel-mediated diminutions in luteinizing hormone, follicle-stimulating hormone, serum and intra-testicular testosterone with concomitant enhancement of sperm production and quality. Further, zinc abrogated nickel-mediated elevation in inflammatory biomarkers including nitric oxide, tumor necrosis factor alpha, interleukin-1 beta as well as caspase-3 activity. The protective influence of zinc on nicked-induced reproductive toxicity was well supported by histological data. Overall, zinc ameliorated nickel-induced reproductive dysfunction